A method for improving the cycle life of pre-lithiated silicon-oxygen anode materials

The alkali resistance of PAA is enhanced by adding crosslinking agent to the prelithiated silicon oxygen battery material, and the problems of volume expansion and alkali resistance are solved, which extends the cycle life of the battery and improves the electrochemical performance.

CN118398774BActive Publication Date: 2025-01-10BLUE OCEAN & BLACK STONE TECH CO LTD (FUJIAN)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410647410.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-23
Publication Date
2025-01-10
Estimated Expiration
2044-05-23

AI Technical Summary

Technical Problem

The prelithiated silicon oxygen material has a short cycle life due to volume expansion in lithium-ion batteries, and the poor alkali resistance of polyacrylic acid (PAA) affects the adhesion and electrode stability, resulting in a degradation of battery performance.

Method used

The crosslinking agent is added during the homogenization of prelithiated silicon oxygen negative electrode material to increase the connection of PAA molecular chains, improve its anti-dissolution and decomposition ability, enhance alkali resistance, thereby inhibiting volume expansion and prolonging cycle life.

Benefits of technology

By improving the alkali resistance and stability of PAA, the cycle life of the battery is extended, the stability and electrochemical performance of the electrode are improved, the internal resistance of the battery is reduced, and the overall performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118398774B_ABST
    Figure CN118398774B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of lithium battery materials, and in particular to a preparation method for improving the cycle life of pre-lithiated silicon oxide negative electrode materials. By adding a cross-linking agent during the homogenization process of the pre-lithiated silicon oxide negative electrode materials, the connection between the PAA molecular chains can be increased, and its anti-dissolution and anti-decomposition capabilities can be improved, thereby enhancing its alkali resistance, achieving a better volume expansion inhibition effect on the pre-lithiated silicon oxide materials, and obtaining better cycle life and pole piece stability. In addition, the method does not change the formula and homogenization process of the pre-lithiated silicon oxide materials, has high process adaptability, and has important application value and promotion prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium battery materials, and in particular to a preparation method for improving the cycle life of pre-lithiated silicon oxide negative electrode materials. Background Art

[0002] As a potential negative electrode material for lithium-ion batteries, silicon-oxygen materials have attracted much attention in the field of energy storage. Silicon and oxygen are abundant elements on the earth, and the raw materials for the production of silicon-oxygen materials are relatively easy to obtain and low in cost. Silicon-oxygen materials will undergo significant volume expansion during the insertion and removal of lithium ions, resulting in deformation and damage to the electrode structure, thereby affecting the cycle stability of silicon-oxygen materials and causing capacity decay and short cycle life of the battery. Therefore, in order to solve the volume expansion problem of silicon-oxygen materials and improve the cycle stability and capacity utilization of the battery, it is necessary to embed lithium ions into silicon-oxygen materials in advance to reduce their volume changes during the charge and discharge process, improve the cycle stability, and thus improve the performance and reliability of the battery.

[0003] Common pre-lithiation methods for silicon oxide materials mainly include solid-state method, solution method and gas phase method. These methods are aimed at pre-embedding lithium ions into silicon oxide materials to reduce the volume expansion problem during the charge and discharge process and improve the cycle stability and capacity utilization of the battery. Solid-state pre-lithiation methods usually include two forms: solid-state reaction and mechanical pre-lithiation. Solid-state reaction is to heat-treat silicon oxide materials with lithium-containing compounds (such as LiH, LiAlH4, etc.) to embed lithium ions into the material lattice. Mechanical pre-lithiation is to mix the lithium source with silicon oxide materials by mechanical ball milling and other methods to allow lithium ions to enter the surface or microscopic defects of the material. Solution methods include sol-gel method and solvothermal method. Sol-gel method is to immerse silicon oxide materials in a solution containing lithium salts. After the sol-gel process, lithium ions are embedded in the material. Solvothermal method is to mix silicon oxide materials with organic solvents containing lithium salts and embed lithium ions into the material through heat treatment. The gas phase pre-lithiation method is to expose the silicon oxide material to a lithium gas environment, so that lithium ions enter the material lattice or surface at high temperature. This method usually requires high temperature and high vacuum conditions.

[0004] Pre-lithiated silicon oxide materials are emerging candidate materials for negative electrode materials of lithium-ion batteries. During the synthesis process, residual alkali, such as solvents and catalysts, may be introduced. This may lead to excessive residual alkalinity on the surface of the silicon oxide materials, resulting in non-uniformity or unstable chemical environment on the surface of the electrode materials, thereby affecting the structural stability and electrochemical properties of the electrode materials, causing the materials to be prone to structural damage during the cycle process, affecting the cycle stability of the battery.

[0005] As a high molecular polymer, polyacrylic acid (PAA) can form a stable bond with silicon-carbon materials, effectively fix silicon particles and carbon materials, and slow down their volume expansion and contraction during the charge and discharge process. However, the residual alkali on the surface of pre-lithiated silicon-oxygen materials has a serious impact on the adhesion of PAA. The residual alkali on the surface of silicon-oxygen materials will affect the adhesion between PAA and silicon-oxygen materials. The residual alkaline substances reduce the adhesion of PAA on the silicon-oxygen surface, resulting in poor adhesion of PAA during the coating process, affecting the quality and performance of electrode coating. In addition, the alkaline substances remaining on the surface of silicon-oxygen materials will also react with the carboxyl groups in PAA to neutralize, change the molecular structure of PAA, and have a negative impact on the cycle stability and charge and discharge performance of silicon-oxygen electrodes in lithium-ion batteries. Therefore, improving the alkali resistance of PAA has become a key technical problem that urgently needs to be solved in the field of silicon-oxygen binders. Summary of the invention

[0006] In view of the technical problem that the existing PAA has poor alkali resistance and leads to poor material service life, the present application provides a preparation method that can improve the cycle life of pre-lithiated silicon oxygen negative electrode materials. By adding a cross-linking agent during the homogenization process of the pre-lithiated silicon oxygen negative electrode material, the connection between the PAA molecular chains can be increased, and its anti-dissolution and anti-decomposition capabilities can be improved, thereby enhancing its alkali resistance, achieving a better volume expansion inhibition effect on the pre-lithiated silicon oxygen material, and obtaining a better cycle life and pole piece stability. In addition, the method does not change the formula and homogenization process of the pre-lithiated silicon oxygen material, has high process adaptability, and is easy to promote and apply on a large scale.

[0007] The present application provides a preparation method for improving the cycle life of a pre-lithiated silicon-oxygen negative electrode material, using the following technical scheme: A preparation method for improving the cycle life of a pre-lithiated silicon-oxygen negative electrode material, comprising the following steps:

[0008] S1, the thickener and the dispersing solvent are stirred evenly, and vacuum degassing is performed to obtain a glue solution;

[0009] S2, adding part of the conductive agent to the glue solution in batches, stirring evenly, and vacuuming and degassing to obtain a conductive slurry;

[0010] S3, adding part of the conductive agent to the negative electrode active material in batches and stirring evenly to obtain a premix;

[0011] S4, adding the conductive paste to the premix and kneading, then adding the binder and stirring and mixing, stirring at 25-60 rpm, 500-1500 rpm, stirring time of 0.5-1h, vacuum degassing, and obtaining a mixed solution;

[0012] S5. Add a cross-linking agent into the mixed solution and stir and mix the mixture to obtain a negative electrode slurry that improves the cycle life of the pre-lithiation silicon oxide negative electrode material.

[0013] By adopting the above technical scheme, in step S1, the uniform stirring of the thickener and the dispersing solvent and the vacuum degassing can effectively ensure the quality and stability of the glue solution, providing a good foundation for the subsequent steps. In step S2, the conductive agent is gradually added to the glue solution, and the conductive slurry is obtained by stirring evenly and vacuum degassing. The preparation process of the conductive slurry ensures that the conductive agent is evenly dispersed in the glue solution, which is beneficial to improving the conductive properties of the negative electrode material. In step S3, the conductive agent is gradually added to the negative electrode active material and stirred evenly to obtain a premix. By fully mixing the conductive agent with the active material, it is beneficial to improve the overall conductive properties of the negative electrode material. In step S4, the conductive slurry is added to the premix and a binder is added to stir and mix. Stirring revolution and rotation can promote the uniform mixing of the components. Vacuum degassing helps to remove bubbles in the mixed solution and ensure the mixing quality. In step S5, a cross-linking agent is added to the mixed solution and stirred and mixed to obtain a negative electrode slurry that improves the cycle life of the pre-lithiation silicon oxygen negative electrode material. The addition of cross-linking agents can increase the connection between PAA molecular chains, improve its alkali resistance, and enhance the stability and cycle life of the material. The synergistic effect between the various steps ensures the quality and stability of the pre-lithiation silicon-oxygen negative electrode material, ultimately improving the performance and cycle life of the battery.

[0014] Preferably, the mass ratio of the negative electrode active material, the conductive agent, the binder, the thickener and the cross-linking agent is (90-96):(1-5):(0.8-2):(0.8-2):(0.8-3); and the solid content of the negative electrode slurry is 35%-55%.

[0015] Preferably, the mass ratio of the negative electrode active material, the conductive agent, the binder, the thickener and the cross-linking agent is (93-95): (3-4.2): (0.9-1.2): (0.9-1.3): (1-1.6); and the solid content of the negative electrode slurry is 40%-50%.

[0016] Preferably, the negative electrode active material is a pre-lithiation silicon oxide material, and the conductive agent is at least one of acetylene black, Ketjen black, carbon nanotubes, graphene and conductive carbon black.

[0017] Preferably, the binder is polyacrylic acid (PAA), the thickener is sodium carboxymethyl cellulose (CMC), and the dispersing solvent is at least one of pure water, ethanol and acetone.

[0018] Preferably, the cross-linking agent is at least one of hydroquinone and resorcinol.

[0019] By adopting the above technical solution, hydroquinone and resorcinol can combine with the hydroxyl groups in polyacrylic acid to form cross-linked bonds, thereby improving the gelling properties of the material, enhancing the mechanical strength and stability of the material, and reducing solubility. The connection between the cross-linking agent and the PAA molecular chain can effectively improve the anti-dissolution and anti-decomposition capabilities, and can slow down the volume expansion rate during the charging and discharging process of the pre-lithiated silicon oxygen negative electrode material, thereby improving the stability and alkali resistance of the material. By adding a cross-linking agent, the pre-lithiated silicon oxygen negative electrode material can be effectively helped to inhibit volume expansion, reduce deformation and damage of the material during the cycle process, and thus extend the cycle life of the battery. Therefore, the addition of a cross-linking agent in the preparation method plays a vital role in improving the cycle life and stability of the pre-lithiated silicon oxygen negative electrode material, and provides strong support for the comprehensive performance of the material.

[0020] Preferably, in step S1, the stirring is performed by using a double planetary stirring kettle for mixing, with a stirring revolution of 40-60rpm, a rotation of 2000-4000rpm, a stirring time of 1-3h, and a material temperature of 25-35°C in the stirring kettle; the process conditions for vacuum degassing are: the degassing vacuum is 0.08-0.1MPa, and the degassing time is 0.5-1h.

[0021] Preferably, in step S2, the stirring is carried out by using a double planetary stirring kettle for mixing, with a stirring revolution of 40-60rpm, a rotation of 2000-4000rpm, a stirring time of 1-3h, and a conductive slurry temperature in the stirring kettle of 25-35°C; the process conditions for vacuum degassing are: the degassing vacuum is 0.08-0.1MPa, and the degassing time is 0.5-1h.

[0022] Preferably, in step S3, the stirring is performed by using a double planetary stirring kettle for mixing, with a revolution of 25-60 rpm and a rotation of 100-1000 rpm, and a stirring time of 1-2 h.

[0023] Preferably, in step S4, the stirring during kneading is performed by using a double planetary stirring kettle for mixing, with a stirring revolution of 40-60rpm, a rotation of 2000-4000rpm, a stirring time of 1-3h, and a material temperature of 30-50°C in the stirring kettle; the process conditions for vacuum degassing are: the degassing vacuum is 0.08-0.1MPa, and the degassing time is 0.5-1h.

[0024] Preferably, in step S5, the stirring and mixing is performed by using a double planetary stirring kettle for mixing, with a stirring speed of 25-60 rpm, a rotation speed of 500-1500 rpm, a stirring time of 0.5-1 h, and a material temperature of 30-50° C. in the stirring kettle.

[0025] By adopting the above technical solution, in step S5, the operating conditions for mixing using a double planetary stirring kettle include a stirring revolution speed of 25-60rpm, a rotation speed of 500-1500rpm, a stirring time of 0.5-1 hour, and a material temperature in the stirring kettle of 30-50°C. These operating conditions play an important role in preparing a negative electrode slurry that improves the cycle life of pre-lithiation silicon oxide negative electrode materials: the stirring structure design of the double planetary stirring kettle enables the material to be stirred and sheared in all directions, which is conducive to the full mixing and dispersion of various components, ensuring that various additives such as cross-linking agents are in full contact with other components, thereby improving the uniformity and stability of the material. By controlling the temperature of the material in the stirring kettle within the range of 30-50°C, it is helpful to control the viscosity and fluidity of the material, promote the reaction of the cross-linking agent with other components, improve the stability and uniformity of the mixed system, and further optimize the material performance. The stirring revolution and rotation speeds and the stirring time are set to promote the complete mixing reaction of the cross-linking agent and other components through mechanical action within a limited time, achieve the best cross-linking effect, and ensure the stability of the material structure and performance optimization. Therefore, by using a double planetary stirring tank for mixing in step S5 and optimizing the stirring parameters and temperature conditions, the mixing reaction between the cross-linking agent and other components can be effectively promoted, the performance of the negative electrode slurry of the pre-lithiation silicon oxide negative electrode material cycle life can be improved, and ultimately the electrochemical performance and cycle stability of the lithium-ion battery can be improved.

[0026] In summary, the beneficial technical effects of this application are:

[0027] 1. Improve cycle life: By adding a cross-linking agent during the homogenization process of the pre-lithiation silicon-oxygen negative electrode material, the connection between the PAA molecular chains is increased, the material's resistance to dissolution and decomposition is improved, and the alkali resistance is enhanced, thereby effectively achieving a better volume expansion inhibition effect on the pre-lithiation silicon-oxygen material. This can improve the cycle life of the material and extend the service life of the lithium-ion battery.

[0028] 2. Improve stability: By strengthening the connection between PAA molecular chains, the stability and anti-polarization peeling ability of the material can be further improved, thereby improving the stability and reliability of the electrode.

[0029] 3. No change in formula and process: This method achieves improved effect without changing the formula and slurry process of pre-lithiation silicon oxide materials. It has high process adaptability and is easy to promote on a large scale and apply in production.

[0030] 4. Improve electrochemical performance: After the prepared pre-lithiation silicon oxide negative electrode material is applied to lithium-ion batteries, the electrochemical performance is significantly improved, including reducing the internal resistance of the battery, improving the cycle performance, etc., effectively improving the battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings used in the embodiments:

[0032] Figure 1 The cycle curves of Example 1, Example 5 and Comparative Example 1 at 1C / 1C room temperature are shown;

[0033] in, Figure 1 A2 is the lithium ion battery obtained in Example 1; Figure 1 A1 is the lithium ion battery obtained in Example 5; Figure 1 A3 is the lithium ion battery obtained in Comparative Example 1. DETAILED DESCRIPTION

[0034] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0035] Example 1

[0036] A preparation method for improving the cycle life of a pre-lithiated silicon-oxygen negative electrode material comprises the following steps:

[0037] S0. Material preparation: The negative electrode active material, acetylene black, polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC) and hydroquinone are prepared in a mass ratio of 90:5:0.8:0.8:0.8, and the negative electrode slurry is prepared with a solid content of 35%. The negative electrode active material is a pre-lithiation silicon oxide material: SiO / C (425 mAh / g);

[0038] S1. Glue preparation: sodium carboxymethyl cellulose (CMC) and pure water are mixed in a double planetary stirring kettle, the stirring is performed at a revolution of 40 rpm and a rotation of 2000 rpm for 3 h, the material temperature in the stirring kettle is 35° C., vacuum degassing is performed, the degassing vacuum is 0.08 MPa, and the degassing time is 0.5 h to obtain a glue solution;

[0039] S2. Preparation of conductive paste: 50% of acetylene black was added to the glue solution in batches, and the mixture was mixed in a double planetary stirring kettle. The stirring speed was 40 rpm, the rotation speed was 2000 rpm, and the stirring time was 3 h. The temperature of the conductive paste in the stirring kettle was 35° C. The conductive paste was vacuumed and degassed at a vacuum of 0.08 MPa for 0.5 h to obtain the conductive paste.

[0040] S3, premix: 50% of acetylene black is added to the pre-lithiated silicon-oxygen material in batches and mixed in a double planetary stirring kettle, with a stirring revolution of 25 rpm and a rotation of 100 rpm for 2 hours to obtain a premix;

[0041] S4, slurry preparation: add the conductive slurry to the premix and knead, use a double planetary stirring kettle to mix, stir at 40 rpm, rotate at 2000 rpm, stir for 3 hours, and the material temperature in the stirring kettle is 50°C; then add polyacrylic acid (PAA) and stir and mix, stir at 60 rpm, rotate at 500 rpm, stir for 1 hour, vacuum degassing, the degassing vacuum is 0.08 MPa, and the degassing time is 0.5 hour to obtain a mixed solution;

[0042] S5. Cross-linking polymerization: Add hydroquinone to the mixed solution, use a double planetary stirring kettle to mix the materials, stir at 25 rpm, 500 rpm, stirring time of 0.5 h, and the material temperature in the stirring kettle is 30°C to obtain a negative electrode slurry that improves the cycle life of the pre-lithiation silicon oxide negative electrode material.

[0043] Example 2

[0044] A preparation method for improving the cycle life of a pre-lithiated silicon-oxygen negative electrode material comprises the following steps:

[0045] S0. Material preparation: The negative electrode active material, carbon nanotubes, polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC) and resorcinol are prepared in a mass ratio of 96:1:2:2:3, and the negative electrode slurry is prepared with a solid content of 55%. The negative electrode active material is a pre-lithiation silicon oxide material: SiO / C (425 mAh / g);

[0046] S1. Glue preparation: sodium carboxymethyl cellulose (CMC) and ethanol are mixed in a double planetary stirring kettle, the stirring revolution is 60 rpm, the rotation is 4000 rpm, the stirring time is 1 h, the material temperature in the stirring kettle is 25° C., vacuum degassing is performed, the degassing vacuum is 0.1 MPa, and the degassing time is 0.5 h to obtain a glue solution;

[0047] S2. Preparation of conductive slurry: 50% of carbon nanotubes were added to the glue solution in batches, and mixed in a double planetary stirring kettle, with a stirring speed of 60 rpm and a rotation speed of 4000 rpm for 1 h. The temperature of the conductive slurry in the stirring kettle was 25°C, and the degassing was performed under vacuum at a vacuum of 0.1 MPa for 1 h to obtain a conductive slurry.

[0048] S3, premix: 50% of carbon nanotubes are added to the negative electrode active material in batches and mixed in a double planetary stirring kettle, with a stirring time of 60 rpm and 1000 rpm, to obtain a premix;

[0049] S4, slurry preparation: add the conductive slurry to the premix and knead it, use a double planetary stirring kettle to mix the materials, stir the revolution of 60 rpm, rotate at 4000 rpm, stir for 1 hour, and the material temperature in the stirring kettle is 30°C; then add polyacrylic acid (PAA) and stir and mix, stir the revolution of 60 rpm, rotate at 1500 rpm, stir for 1 hour, vacuum degassing, the degassing vacuum is 0.1 MPa, and the degassing time is 1 hour to obtain a mixed solution;

[0050] S5. Cross-linking polymerization: Add resorcinol to the mixed solution, and use a double planetary stirring kettle to mix the materials. The stirring speed is 60 rpm, the rotation speed is 1500 rpm, the stirring time is 1 hour, and the material temperature in the stirring kettle is 50°C to obtain a negative electrode slurry that improves the cycle life of the pre-lithiation silicon oxide negative electrode material.

[0051] Example 3

[0052] A preparation method for improving the cycle life of a pre-lithiated silicon-oxygen negative electrode material comprises the following steps:

[0053] S0. Material preparation: The negative electrode active material, Ketjen black, polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC) and hydroquinone are prepared in a mass ratio of 93:3:0.9:0.9:1, and the negative electrode slurry is prepared with a solid content of 40%. The negative electrode active material is a pre-lithiation silicon oxide material: SiO / C (425 mAh / g);

[0054] S1. Glue preparation: sodium carboxymethyl cellulose (CMC) and acetone are mixed in a double planetary stirring kettle, the stirring revolution is 50 rpm, the rotation is 3000 rpm, the stirring time is 2 h, the material temperature in the stirring kettle is 30° C., vacuum degassing is performed, the degassing vacuum is 0.089 MPa, and the degassing time is 0.8 h to obtain a glue solution;

[0055] S2. Preparation of conductive paste: 50% of Ketjen black was added to the glue solution in batches, and the mixture was mixed in a double planetary stirring kettle. The stirring speed was 50 rpm, the rotation speed was 3000 rpm, and the stirring time was 2 h. The temperature of the conductive paste in the stirring kettle was 30° C. The conductive paste was vacuumed and degassed at a vacuum of 0.09 MPa for 0.8 h to obtain the conductive paste.

[0056] S3, premix: 50% of Ketjen black is added to the pre-lithiated silicon-oxygen material in batches and mixed in a double planetary stirring kettle, with a stirring revolution of 50 rpm and a rotation of 500 rpm for 1.5 h to obtain a premix;

[0057] S4, slurry preparation: add the conductive slurry to the premix and knead it, use a double planetary stirring kettle to mix the materials, stir the revolution of 50 rpm, rotate at 3000 rpm, stir for 2 hours, and the material temperature in the stirring kettle is 40°C; then add polyacrylic acid (PAA) and stir and mix, stir the revolution of 50 rpm, rotate at 900 rpm, stir for 0.8 hours, vacuum degassing, the degassing vacuum is 0.09 MPa, and the degassing time is 0.8 hours to obtain a mixed solution;

[0058] S5. Cross-linking polymerization: Add hydroquinone to the mixed solution, and use a double planetary stirring kettle to mix the materials. The stirring speed is 50 rpm, the rotation speed is 900 rpm, the stirring time is 0.8 h, and the material temperature in the stirring kettle is 40°C to obtain a negative electrode slurry that improves the cycle life of the pre-lithiation silicon oxide negative electrode material.

[0059] Example 4

[0060] S0. Material preparation: The negative electrode active material, conductive carbon black, polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC) and hydroquinone are prepared in a mass ratio of 95:4.2:1.2:1.3:1.6, and the negative electrode slurry is prepared with a solid content of 40%. The negative electrode active material is a pre-lithiation silicon oxide material: SiO / C (425 mAh / g);

[0061] S1. Glue preparation: sodium carboxymethyl cellulose (CMC) and acetone are mixed in a double planetary stirring kettle, the stirring revolution is 50 rpm, the rotation is 3000 rpm, the stirring time is 2 h, the material temperature in the stirring kettle is 30° C., vacuum degassing is performed, the degassing vacuum is 0.089 MPa, and the degassing time is 0.8 h to obtain a glue solution;

[0062] S2. Preparation of conductive slurry: 50% of conductive carbon black was added to the glue in batches, and the mixture was mixed in a double planetary stirring kettle. The stirring speed was 50 rpm, the rotation speed was 3000 rpm, and the stirring time was 2 h. The temperature of the conductive slurry in the stirring kettle was 30° C. The conductive slurry was vacuumed and degassed at a vacuum of 0.09 MPa for 0.8 h to obtain the conductive slurry.

[0063] S3, premix: 50% of the conductive carbon black is added to the pre-lithiated silicon-oxygen material in batches and mixed in a double planetary stirring kettle, with a stirring revolution of 50 rpm and a rotation of 500 rpm for 1.5 h to obtain a premix;

[0064] S4, slurry preparation: add the conductive slurry to the premix and knead it, use a double planetary stirring kettle to mix the materials, stir the revolution of 50 rpm, rotate at 3000 rpm, stir for 2 hours, and the material temperature in the stirring kettle is 40°C; then add polyacrylic acid (PAA) and stir and mix, stir the revolution of 50 rpm, rotate at 900 rpm, stir for 0.8 hours, vacuum degassing, the degassing vacuum is 0.09 MPa, and the degassing time is 0.8 hours to obtain a mixed solution;

[0065] S5. Cross-linking polymerization: Add hydroquinone to the mixed solution, and use a double planetary stirring kettle to mix the materials. The stirring speed is 50 rpm, the rotation speed is 900 rpm, the stirring time is 0.8 h, and the material temperature in the stirring kettle is 40°C to obtain a negative electrode slurry that improves the cycle life of the pre-lithiation silicon oxide negative electrode material.

[0066] Example 5

[0067] The same as Example 4, except that: S0, preparation: the mass ratio of the negative electrode active material, conductive carbon black, polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC) and hydroquinone is 93:3.5:1:1:1.5, the negative electrode slurry is prepared with a solid content of 40%, and the negative electrode active material is a pre-lithiation silicon oxide material SiO / C (425mAh / g).

[0068] Comparative Example 1

[0069] S0. Material preparation: The negative electrode active material, conductive carbon black, polyacrylic acid (PAA) and sodium carboxymethyl cellulose (CMC) are prepared in a mass ratio of 93:3.5:1:1, and the negative electrode slurry is prepared with a solid content of 40%. The negative electrode active material is a pre-lithiation silicon oxide material: SiO / C (425 mAh / g);

[0070] S1. Glue preparation: sodium carboxymethyl cellulose (CMC) and acetone are mixed in a double planetary stirring kettle, the stirring revolution is 50 rpm, the rotation is 3000 rpm, the stirring time is 2 h, the material temperature in the stirring kettle is 30° C., vacuum degassing is performed, the degassing vacuum is 0.089 MPa, and the degassing time is 0.8 h to obtain a glue solution;

[0071] S2. Preparation of conductive slurry: 50% of conductive carbon black was added to the glue in batches, and the mixture was mixed in a double planetary stirring kettle. The stirring speed was 50 rpm, the rotation speed was 3000 rpm, and the stirring time was 2 h. The temperature of the conductive slurry in the stirring kettle was 30° C. The conductive slurry was vacuumed and degassed at a vacuum of 0.09 MPa for 0.8 h to obtain the conductive slurry.

[0072] S3, premix: 50% of the conductive carbon black is added to the pre-lithiated silicon-oxygen material in batches and mixed in a double planetary stirring kettle, with a stirring revolution of 50 rpm and a rotation of 500 rpm for 1.5 h to obtain a premix;

[0073] S4. Slurry preparation: Add the conductive slurry into the premix and knead it. Use a double planetary stirring kettle to mix the materials. The stirring speed is 50 rpm, the rotation speed is 3000 rpm, the stirring time is 2 hours, and the material temperature in the stirring kettle is 40°C. Then add polyacrylic acid (PAA) and mix. The stirring speed is 50 rpm, the rotation speed is 900 rpm, and the stirring time is 0.8 hours. Vacuum degassing is performed. The degassing vacuum is 0.09 MPa and the degassing time is 0.8 hours to obtain a negative electrode slurry that improves the cycle life of the pre-lithiation silicon oxide negative electrode material.

[0074] Performance Testing

[0075] The negative electrode slurries for improving the cycle life of pre-lithiated silicon oxide negative electrode materials prepared in Examples 1 to 5 and Comparative Example 1 were made into lithium-ion batteries in the following manner and subjected to electrochemical tests; wherein the lithium-ion batteries obtained in Example 1, Example 5 and Comparative Example 1 were labeled A2, A1 and A3, respectively.

[0076] (1) Preparation of positive electrode sheet: The prepared positive electrode slurry is evenly coated on the front and back sides of the aluminum foil, and then dried, rolled, and die-cut to form a positive electrode sheet. The coating double-sided surface density is 50 mg / cm 2 ;

[0077] (2) Prepare the negative electrode sheet. Evenly coat the prepared negative electrode slurry on the front and back of the copper foil, dry, roll and die-cut to make the negative electrode sheet. The coating double-sided surface density is 22 mg / cm 2 .

[0078] (3) Preparation of high energy density lithium-ion batteries: The aforementioned positive electrode sheets, negative electrode sheets and separators are stacked to form bare cells. After short-circuit testing, they are welded to the tabs, sealed on the top and sides, baked, injected, formed, sealed and divided into two parts to form soft-pack lithium-ion batteries.

[0079] Electrochemical testing

[0080] 1. DC internal resistance test: At room temperature 25±1℃, charge to 4.25V with 1C constant current, then charge with constant voltage, with the cut-off current at 0.05C and stand for 3H, record the voltage V0; discharge with 5C constant current for 3s, record the voltage after 3s as V1, DC internal resistance DCR = (V0-V1) / 5C;

[0081] 2. Cycle life test: At room temperature 25±1℃, charge at 1C constant current to 4.25V, then charge at constant voltage, let stand for 10min at a cut-off current of 0.05C, discharge at 1C constant current to 2.75V, cycle 500 times, with an interval of 10min between each charge and discharge, record the capacity and calculate the capacity retention rate (discharge capacity after cycle / discharge capacity in the first cycle).

[0082] The test results are shown in Table 1. The cycle curves of the lithium ion batteries obtained in Example 1, Example 5 and Comparative Example 1 at room temperature are shown in Table 1. Figure 1 shown.

[0083] Table 1 Electrochemical performance test results

[0084]

[0085] It can be seen from Table 1 that the pre-lithiation silicon oxide negative electrode material obtained in the present application is used to make a lithium-ion battery, and its electrochemical performance, battery cell internal resistance, cycle performance, etc. are greatly improved.

[0086] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a pre-lithiated silicon-oxygen negative electrode material for improving the cycle life, characterized in that: The following steps are involved: S1, the thickener and the dispersing solvent are stirred evenly, and vacuum degassing is performed to obtain a glue solution; S2, adding part of the conductive agent to the glue solution in batches, stirring evenly, and vacuuming and degassing to obtain a conductive slurry; S3, adding part of the conductive agent to the negative electrode active material in batches and stirring evenly to obtain a premix; S4, adding the conductive paste to the premix and kneading, then adding the binder and stirring and mixing, stirring at 25-60 rpm, 500-1500 rpm, stirring time of 0.5-1h, vacuum degassing, and obtaining a mixed solution; S5, adding a cross-linking agent to the mixed solution and stirring and mixing, so as to obtain a negative electrode slurry for improving the cycle life of the pre-lithiation silicon oxygen negative electrode material; The mass ratio of the negative electrode active material, the conductive agent, the binder, the thickener and the cross-linking agent is (90-96): (1-5): (0.8-2): (0.8-2): (0.8-3); the solid content of the negative electrode slurry is 35%-55%; The mass ratio of the negative electrode active material, the conductive agent, the binder, the thickener and the cross-linking agent is (93-95): (3-4.2): (0.9-1.2): (0.9-1.3): (1-1.6); the solid content of the negative electrode slurry is 40%-50%; The negative electrode active material is a pre-lithiation silicon-oxygen material, and the conductive agent is at least one of acetylene black, Ketjen black, carbon nanotubes, graphene and conductive carbon black; The binder is polyacrylic acid (PAA), the thickener is sodium carboxymethyl cellulose (CMC), the dispersing solvent is at least one of pure water, ethanol and acetone, and the cross-linking agent is at least one of hydroquinone and resorcinol; In step S1, the stirring is performed by using a double planetary stirring kettle for mixing, the stirring revolution is 40-60rpm, the rotation is 2000-4000rpm, the stirring time is 1-3h, and the material temperature in the stirring kettle is 25-35°C; the process conditions of the vacuum degassing are: the degassing vacuum is 0.08-0.1MPa, and the degassing time is 0.5-1h; In step S2, the stirring is performed by using a double planetary stirring kettle for mixing, the stirring revolution is 40-60rpm, the rotation is 2000-4000rpm, the stirring time is 1-3h, and the temperature of the conductive slurry in the stirring kettle is 25-35°C; the process conditions of the vacuum degassing are: the degassing vacuum is 0.08-0.1MPa, and the degassing time is 0.5-1h; In step S3, the stirring is performed by using a double planetary stirring kettle for mixing, with a stirring speed of 25-60 rpm, a rotation speed of 100-1000 rpm, and a stirring time of 1-2 h; In step S4, the stirring during kneading is performed by using a double planetary stirring kettle for mixing, the stirring revolution is 40-60rpm, the rotation is 2000-4000rpm, the stirring time is 1-3h, and the material temperature in the stirring kettle is 30-50°C; the process conditions for vacuum degassing are: the degassing vacuum is 0.08-0.1MPa, and the degassing time is 0.5-1h; In step S5, the stirring and mixing is performed by using a double planetary stirring kettle for mixing, with a stirring revolution of 25-60 rpm, a rotation of 500-1500 rpm, a stirring time of 0.5-1 h, and a material temperature of 30-50° C. in the stirring kettle.

Citation Information

Patent Citations

  • Preparation method of lithium battery slurry and application thereof

    CN110061222A

  • Slurry composition for lithium ion secondary battery negative electrode and manufacturing method thereof, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2014089834A